2011
DOI: 10.1093/jac/dkr386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epidemiological characterization of HIV-1 infection networks involving transmitted drug resistance mutations in Northern Greece

Abstract: Our findings underline the substantial impact of transmission networks on TDR in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
6
16
1
Order By: Relevance
“…In the present study we found a substantial increase in the levels of TDR among newly diagnosed antiretroviral naive HIV‐1‐infected individuals in our region from 2009 to 2011 compared with the period 2000–07 (21.8% vs 12.5%) . This increase was driven by an increase in NNRTI (18.9% vs 5.4%) and NRTI resistance (14.3% vs 7.6%); a reduction was observed in protease inhibitor resistance (1.2% vs 3.3%).…”
Section: Discussionsupporting
confidence: 45%
“…In the present study we found a substantial increase in the levels of TDR among newly diagnosed antiretroviral naive HIV‐1‐infected individuals in our region from 2009 to 2011 compared with the period 2000–07 (21.8% vs 12.5%) . This increase was driven by an increase in NNRTI (18.9% vs 5.4%) and NRTI resistance (14.3% vs 7.6%); a reduction was observed in protease inhibitor resistance (1.2% vs 3.3%).…”
Section: Discussionsupporting
confidence: 45%
“…Similar results were reported in various countries for different subtypes, with most common transmission of NRTI DRMs [22], [41], [42], [43]. As expected, no integrase inhibitor (InI) transmitted resistance was found, which is consistent to the fact that all infections were acquired before introduction of InI in the clinical practice.…”
Section: Discussionsupporting
confidence: 88%
“…Prevalence of major protease and reverse transcriptase mutations is similar across the variants, however both virologic and immunologic treatment efficacy is similar to the subtype B [19], [20]. In general, frequency of primary drug resistance differs locally in Europe, often being associated with transmission clusters, fluctuates over time and is usually limited to a single class of antiretrovirals [21], [22], [23], [24]. In Poland the prevalence of transmitted drug resistance in the years 2006–2009 ranged from 3.9% to 7.4% [25].…”
Section: Introductionmentioning
confidence: 99%
“…Because other studies consistently showed regional differences between the drivers of the HIV-1 epidemic [13], [14], this study aimed to characterize the temporal trend in TDR, the factors associated with TDR including TCs and the clinical impact of TDR for a period of 15 years in a regional epidemic, serviced by the Leuven University Hospitals. The data included socio-demographic, clinical and virological variables.…”
Section: Introductionmentioning
confidence: 99%